ORGANIZATIONAL INTEGRITY OF THE DEPARTMENT OF ENVIRONMENT AND NATURAL RESOURCES IN NUEVA VIZCAYA: IT’S CORRELATION WITH EMPLOYEES’ ORGANIZATIONAL LOYALTY AND HOLISTIC JOB FULFILMENT - GIOVANNIEM. MAGAT; IMELDAS. OCAMPO, PhD (International Journal of Educational Excellence and Innovation, 2024)
This research investigated the organizational dynamics within the Department of Environment and Natural Resources (DENR) in Nueva Vizcaya, with a focus on organizational integrity, organizational loyalty, and holistic job fulfillment. A quantitative, descriptive-correlational research design was employed to explore the relationships among these variables. The study involved 105 respondents, representing 73.43% of the total workforce of 143 employees, determined using the Slovin Formula, a common statistical method for calculating sample sizes based on a desired margin oferror. Data were gatheredthrough validated andreliable research instruments, and the results were analyzed using appropriate statistical tools. The findings revealed that the DENR-Nueva Vizcaya exhibits a generally satisfactory level of organizational integrity, especially in the areas of ethical leadership and community engagement. However, significant improvements are needed in aspects of transparency and accountability. In terms of organizational loyalty, employees rated it as "Good," with a strong sense of cultural and leadership loyalty, although ethical loyalty and mission commitment were identified as areas for enhancement. Holistic job fulfillment was also rated positively, particularly in the domains of job motivation and satisfaction, but there is a need to improve employee engagement and job enrichment to fully realize overall fulfillment. Moreover, the study uncovered a strong positive relationship between perceived organizational integrity and organizational loyalty, indicating that as employees perceive higher integrity in their organization, their loyalty increases. A moderate yet significant relationship was also observed between organizational integrity and holistic job fulfillment, suggesting that better integrity leads to improved job satisfaction. Mostnotably, a very strong positive correlation wasfound between organizational loyalty and holistic job fulfillment, implying that higher loyalty correlates with greater overall job satisfaction. Based on the seinsights, the researcher developed a set of targeted training programs designed to address the identified gaps, focusing on enhancing transparency, accountability, ethical loyalty, and employee engagement. Additionally, fostering a culture of continuous improvement through regular policy reviews and employee participation in decision-making was recommended to strengthen organizational excellence.